KNOWLEDGE AND ATTITUDE TOWARDS PERINATAL ORAL HEALTH CARE AMONG NURSING STUDENTS - Patil Disha; Mohanraj Kamatchi; Prathima GS; Kavya Rani BS; Deeksha Sharma; Jasmine Mary Antony; Shruti Virupaxi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aim and background: Expectant women are more susceptible to oral health problems during pregnancy. Among various healthcare professionals, nurses are more likely to see pregnant women and their infants than dentists. It is imperative that nurses have a good basic knowledge on perinatal oral health and associated risk factors for dental caries and ECC, and are willing and able to advise pregnant women. Henceforth, this study aimed to examine the baseline knowledge and attitude of undergraduate nursing students during their formative years of healthcare professional education.Materials and methods: A cross sectional study was conducted among 100 nursing students in Vivekanandha college of Nursing. Data was collected using predefined data capture form / schedule / questionnaire. Privacy and Confidentiality was maintained. The obtained data was transferred to the MS-EXCEL Sheet and descriptive statistics was carried out.Results: More than two third (82%) were unaware that suppressing maternal oral microorganism reservoirs can decrease the infants risk of developing ECC. 57% agreed and 3% strongly agreed that they should update their knowledge on perinatal oral health and associated risk factors of dental caries and ECC.Conclusion: Nursing students had limited knowledge about oral health of pregnant women and had some misunderstandings about oral health, although they had good attitudes.